Conductivity of melt spun PMMA composites with aligned carbon fibers - Qu, Muchao; Schubert, Dirk W. (Composites Science and Technology, 2016)
The conductivity and morphology of melt-spun PMMA/carbon fiber (CF) composites have been investigated and analyzed. Using a two-step melt mixing procedure, CF aspect ratios of 6.3, 9.2 and 12.0 were achieved. Fiber composites with different CFs concentrations were melt spun using a capillary rheometer, to induce CF orientation, and the morphologies of both the surface and the cross-section were observed and discussed. The conductivity of composite fibers at room temperature was compared with the McLachlan GEM equation and Balberg excluded volume theory. The percolation threshold as well as the relationship between the percolation behavior and the aspect ratio were also determined. Taking into consideration the filler orientation, the slope K = 3.4 in excluded volume theory was estimated for the first tim